REVOLUTIONIZING ENTERPRISE AUDITING THROUGH BIG DATA UTILIZATION - Jennings, Sarah (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
Grassroots governance is a vital component of a nation's governance framework, with its effectiveness directly impacting national and societal goals, as well as the well-being of its citizens. The digital age has ushered in an era of transformation for grassroots governance, with the Communist Party of China (CPC) Central Committee placing significant emphasis on the development of "Digital China." This initiative integrates cuttingedge technologies such as artificial intelligence, big data, blockchain, and the internet into grassroots government operations. The 20th National Congress of the Communist Party of China underscored the importance of constructing a "Digital China" as a key element in achieving modern socialist goals in the digital era. In February 2023, the CPC Central Committee and the State Council unveiled the "Overall Layout Plan for the Construction of Digital China," emphasizing that building a digital China is pivotal for advancing Chinese-style modernization, gaining a competitive edge nationally, and accelerating the establishment of a new development paradigm. Grassroots digital governance is an integral component of the broader "Digital China" initiative. It leverages digital technologies to empower and advance grassroots governance towards digitalization, intelligence, and precision. Sichuan and Guizhou Provinces have made notable progress in developing and applying digital governance platforms, serving as valuable models for the nation. This paper examines their experiences, identifies existing challenges, and offers practical recommendations to enhance and propel the digital transformation and governance platform construction. It aims to contribute to the modernization of the national governance system and capabilities